Optimizing contribution rate of socso’s invalidity pension scheme (IPS): an actuarial present value (APV) modelling / Mohd Zaki Awang Chek - Awang Chek, Mohd Zaki (Institute of Graduate Studies, UiTM, 2017)
This dissertation proposes the optimisation of the contribution rate for Social Security Organisation (SOCSO)’s Invalidity Pension Scheme (IPS). In performing this study, four objectives were set. Firstly, this study aims to statistically analyse the current situation of the contribution fund collection and the claim benefits payment under SOCSO’s IPS. Secondly, it seeks to develop an actuarial formulation based on the benefits coverage from SOCSO’s IPS. Thirdly, it attempts to determine an optimal contribution rate to support the benefits provided under SOCSO’s IPS using an actuarial approach. Fourthly, it proposes an appropriate contribution rate to be implemented by SOCSO. Currently, the contribution rate for SOCSO’s IPS is 1%, which is shared equally between employer and employee. This contribution rate is directly deducted from the employee’s monthly gross salary. This contribution rate needs to be adjusted upwards by SOCSO in the near future to ensure that all payments of claims are sufficiently covered.